Gene Expression Sets and Renal Profiling from the Renal AL Amyloid Involvement and NEOD00 (RAIN) Trial - Cindy Varga; Felix Eichinger; Viji Nair; Abhijit S. Naik; Samih H. Nasr; Agnes B. Fogo; Denis Toskic; Matthias Kretzler; Raymond L. Comenzo (Kidney International Reports)
Introduction: There is an unmet need to understand the mechanisms by which amyloid deposition drives alterations in the kidney. We leveraged renal biopsies from amyloid light-chain (AL) amyloidosis participants of the Renal AL Amyloid Involvement and NEOD00 (RAIN) trial (NCT03168906) to perform transcriptional profiling and to employ a novel histologic scoring tool. Our objective was to utilize a transcriptome-driven approach to identify AL molecular signatures that may be prognostic. Methods: Clinical data were correlated to histologic and molecular findings. A composite scarring injury and amyloid score (AS) were assigned to each biopsy. Glomerular and tubulointerstitial (TI) compartments were microdissected and sequenced separately. Expression data were compared to healthy living donors and focal segmental glomerulosclerosis (FSGS) profiles. Differentially expressed genes were determined. Results: Cluster analysis revealed 2 distinct patient clusters (G1 and G2) based on gene expression. The AS was higher in the TI compartment (6.5 vs. 4.5; P = 0.0290) of G2. Glomeruli showed activation of fibrotic pathways and increased canonical signaling of LPS/IL-1. TNF activation was noted in TI. Enriched ingenuity canonical pathways included “coagulation system,” “GADD45 signaling,” and “Wnt/Ca+ pathway,” among others. For AL versus living donors, ingenuity pathway analysis identified enrichment in PI3K/Akt signaling. Gene regulators of cellular proliferation were enriched in the amyloid group. Conclusion: Despite the small sample size, we identified 2 distinct groups of patients with AL based on molecular signatures. Detailed studies of a larger cohort encompassing omics technologies at a single cell resolution will further help to identify the response of individual kidney cell types to amyloid deposits, potentially leading to the development of novel therapeutic targets.